Implementation of the Use of Educational Video Media in Developing Stop Bullying Behavior in Early Child-hood Education - Rahmawati, R; Hastuti, Isnaini Budi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to analyze the effectiveness of using educational video media in developing anti-bullying behavior among kindergarten students at Aisyiyah Kragilan Surakarta. It seeks to determine the extent to which educational videos influence students' understanding and behavior regarding bullying. Methodology: A descriptive qualitative approach was employed, involving 30 children aged 5–6 years, as well as teachers and parents as participants. Data collection methods included observation, interviews, and documentation. Triangulation was used in data analysis through the stages of data reduction, data presentation, and conclusion drawing. Results: The study found a noticeable improvement in students' understanding and behavioral change after exposure to educational video media. It revealed the negative impacts of bullying on both victims (such as physical and mental health issues and developmental disruptions) and perpetrators (including poor personality development and social rejection). The video media proved to be effective in promoting anti-bullying behavior among the children. Applications/Originality/Value: The findings underscore the importance of digital educational media in early childhood education, especially for shaping positive social behavior. This research contributes to the understanding that incorporating digital tools, like educational videos, can enhance moral development in young learners. It also emphasizes the role of adequate school facilities and infrastructure in ensuring the success of such learning programs.